2017
DOI: 10.1002/jsfa.8234
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary macronutrients on aflatoxicosis: a mini‐review

Abstract: Aflatoxin is a toxin produced by Aspergillus species of fungi. The main route of aflatoxin exposure is through the diet. Indeed, long-term aflatoxin exposure is linked to the development of hepatocellular carcinoma (HCC). Aflatoxin causes aflatoxicosis, which can be affected by several factors and is prevalent in many developing Asian and African countries. This mini-review discusses the effects of carbohydrate, fat and protein on aflatoxicosis based on findings from animal and human studies. It was found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
(99 reference statements)
0
8
0
Order By: Relevance
“…AFB 1 can cause weight loss and reduce food consumption by reducing the level of leptin [ 21 ], which directly affects the energy balance and body weight gain [ 22 ]. In the present study, no significant difference on the body weight gain was observed between group A (58.5 ± 4.6 g) and group C (53.33 ± 7.9 g), as the HP diet enhances detoxification of AFB 1 [ 12 ]. However, rats in groups B (47.67 ± 5.5 g) had significantly lower weight gain ( p < 0.05) compared to rats in group A.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…AFB 1 can cause weight loss and reduce food consumption by reducing the level of leptin [ 21 ], which directly affects the energy balance and body weight gain [ 22 ]. In the present study, no significant difference on the body weight gain was observed between group A (58.5 ± 4.6 g) and group C (53.33 ± 7.9 g), as the HP diet enhances detoxification of AFB 1 [ 12 ]. However, rats in groups B (47.67 ± 5.5 g) had significantly lower weight gain ( p < 0.05) compared to rats in group A.…”
Section: Resultsmentioning
confidence: 71%
“…A possible explanation of this finding could be due to the type of diet. As previously mentioned, HP diet enhances detoxification of AFB 1 [ 12 ]. HP diet also has effect on the hepatic enzymes as found in an animal study [ 34 ].…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Lipid metabolism disorders might be to some extent related to oxidative stress (Galhardi et al, 2004;Lu et al, 2011). The effect of AFB1 on the development of HCC might be described through p53 gene mutations as well as concomitant hepatitis B virus infection (Nurul Adilah & Mohd Redzwan, 2017). Aflatoxin B1 ends up with a GC to TA transversion in codon 249 of the human p53 (Aguilar, Hussain, & Cerutti, 1993).…”
Section: Livermentioning
confidence: 99%
“…Because A. parasiticus and A. flavus usually multiply under hot and humid conditions, AFB1 is as a contaminant of human food (including core, peanuts, soya sauce, and fermented soy beans) in tropical areas [1][2][3][4]. Increasing evidence has shown that AFB1 has three toxicological effects: (a) the attraction of specific organs, especially liver; (b) genotoxicity, mainly inducing the formation of the hot-spot mutation of p53 gene (especially mutation at the codon 249) and AFB1-DNA adducts; and (c) carcinogenicity, primarily causing hepatocellular carcinoma (HCC) [4][5][6][7][8][9][10][11]. Studies have shown that DNA damage induced by AFB1 plays the central role of carcinogenesis of HCC related to AFB1 in the toxic studies [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%